Spatial-cognition ontology models in policymaking: dealing with urban landmarks in literary narratives - Stufano Melone, Maria Rosaria Rossella; Camarda, Domenico (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Urban complexity is expressed through multiple and multiform directions and dimensions. With the aim of operationally managing such complexity, scholars have recently started uneasy research toward the construction of system architectures to support informed and aware policymaking. In particular, agent-based modelling efforts have been developed using the so-called applied ontologies. These models appear promising towards supporting complex relational and cognitive interactions in processes of urban decisions. Increasing simulation and experimentation activities are now oriented towards the support of ontology-based spatial planning processes in the real world. In the current planning context, where natural discourses and narrations are embedded in participatory plans, useful answers can also be provided by the narrations of some literary works, in the aforementioned sense. The work we have carried out explores the spatial representations included in those narratives, trying to develop ontological analyzes based on complex structuring characters and features of the represented urban spaces. The work is based on multi-agent experiments carried out with university students, who have extracted some passages from literary works dealing with urban environments. In particular, the paper analyzes some narratives focused on the urban square (or 'piazza'), with the aim of drawing out an ontology of it including aspects of literary semantics.